Do IMF and World Bank programs induce government crises An empirical analysis - Axel Dreher; Martin Gassebner (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
We examine whether and under which circumstances World Bank projects and IMF programs affect the likelihood of major government crises. Using a sample of more than 90 developing countries over the period 1970-2002, we find that crises are on average more likely in the presence of Bank and Fund involvement. While the effect of the IMF to some extent depends on the model specification, the impact of the World Bank is shown to be robust to the choice of control variables and method of estimation. We also find that governments face an increasing risk to enter a crisis when they remain under IFI programs when the economy performs better. The (economic) conditions present when a new IFI program is initiated, however, do not play a major role for crisis probability. Finally, only programs concluded by the current government affect crises, while those inherited by preceding governments do not.
Keywords: D72; F34; P48; 330; Political Crisis; International Financial Institutions